Hubungan Dukungan Sosial Dengan Manajemen Diri Penderita DM Tipe 2 Selama Pandemi Covid-19 - Rahmadiya, Siska; Herawati, Tuti; Kurnia, Dikha Ayu (Universitas Fort De Kock Bukittinggi, 2024)
Background: Diabetes Mellitus (DM) is a chronic degenerative disease that cannot be cured but can be controlled with routine care. The COVID-19 pandemic imposes a policy of limiting physical activity so that people with Type 2 Diabetes Mellitus experience difficulties in physical activity, fulfilling food and medicine needs access to health services and lack of self-awareness of checking blood sugar, so that people with diabetes mellitus experience a decrease in their ability to carry out self-care. Self-management is a drive or motivation that comes from within and outside the individual to achieve certain goals in managing and organizing themselves as well as possible. Social support has a major effect on the well-being of people with type 2 DM. Getting social support helps people with type 2 diabetes better control their disease.Methods: This quantitative study used a cross-sectional approach. The target population is Type 2 DM clients who seek treatment at the IV Koto Health Center. The sample in this study were all Type 2 DM patients selected in this study as many as 88 people. Data collection through questionnaires. The research instruments were the Summary Of Diabetes Self Care Activities Revised (SDSCA) Questionnaire and the S4-MAD Questionnaire for social support. Researchers conducted bivariate analysis, namely with self-management with a categorical data scale and the dependent variable was self-management so that the test used was the chi-Square test. As for age and length of suffering using the t test and Mann Whitney test. Results: The statistical test results of social support on good self-management obtained p value 0.010 which means there is a relationship between social support and self-management there are 53 people (93.0%) of 88 respondents who get less social support to do good self-management